2020
DOI: 10.1093/ofid/ofaa508
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Bacterial Contamination from Patients on Contact Precaution in Operating Room Environment

Abstract: We investigated the microbial burden on the operating room environment when patients on contact precautions for a multidrug-resistant pathogen received surgery. Our study demonstrated that the perioperative environment was contaminated with aerobic bacteria and MRSA after surgery, and that MRSA persisted environmentally even after cleaning/disinfection, highlighting the need for meticulous cleaning/disinfection in the perioperative environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Sources of environmental contaminants include the skin, hair, and hands of healthcare professionals or the physical environment, such as operating tables, auxiliary tables, and anesthesia machines. 20 In this study, we observed the growth of the main microorganisms of epidemiological importance at different incubation times and sample collection sites. These results were consistent with the findings of previous studies on the contamination of the inspiratory and expiratory branches 21 that may be associated with processing that proves ineffective in disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of environmental contaminants include the skin, hair, and hands of healthcare professionals or the physical environment, such as operating tables, auxiliary tables, and anesthesia machines. 20 In this study, we observed the growth of the main microorganisms of epidemiological importance at different incubation times and sample collection sites. These results were consistent with the findings of previous studies on the contamination of the inspiratory and expiratory branches 21 that may be associated with processing that proves ineffective in disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…De igual manera la contaminación en las áreas de quirófano es una de las áreas más representativa en el estudio, en las que se indican reportes en colonización de estafilococos, especialmente en vías respiratorias (23). Otros estudios muestran que este patógeno persiste incluso luego de una limpieza y desafección de quirófano con muestras positivas tomadas durante el periodo peri operatorio (24). Además, Sánchez, A., Rincón., et al, en el área de pediatría y otras investigaciones previas.…”
Section: Discussionunclassified
“…Some have found that cleaning does not accurately predict disinfection, as determined by surface microbial colony counts, even if antimicrobial products are used. 3,29,30 We did not specifically measure disinfection, but over the 10-year period of improving environmental cleaning, we experienced a 75% reduction in overall hospitalacquired infection (HAI) rates, 55% reductions in class I and II surgical site infection (SSI) rates, and a 70% reduction in hospital-onset C. difficile rates. Other studies have also shown a reduction in HAIs with enhanced cleaning and associated disinfection.…”
Section: Discussionmentioning
confidence: 99%